A Filmagem de Apresentações Orais: Desenvolvimento da Consciência da Competência Oral nos Aprendentes de Língua Estrangeira. - Raquel Carlos Carvalho e Couto (2012)
This action research intends to help the students to develop their awareness of the strengths and weaknesses of their oral presentations in a foreign language, guiding them to reflect more deeply on their performance, in order to be able to improve it. The video camera is the most important data-gathering tool for the implementation of this project, enabling both the teacher and the students to observe the presentations more thoroughly. The analysis resulting from that observation is, undoubtedly, essential to developing the process of awareness. This process is comprised by a first moment of self-evaluation, followed by peer evaluation and culminating in the teacher's feedback, commenting on the students' observations with the aim of enriching this analysis in order to help students improve their performance.